Whistleblowers as Anti-Fraud in Banking Crimes from a Maslahah Perspective - Zaid Alfauza Marpaung; Mhd Syahnan; Budi Sastra Panjaitan (Hukum Keluarga Islam IAIN LANGSA, 2025)
This research aims to examine the important role of whistleblowers in exposing banking crimes from the perspective of maslahah in Islamic law. The study employs a qualitative-normative approach using a literature review method based on positive legal regulations and scholarly works related to maslahah theory developed by maqasid scholars. The legal sources consist of primary legal materials such as the Corruption Crime Law, the Financial Services Authority, and the Law on the Protection of Witnesses and Victims, as well as secondary legal materials in the form of books, journals, and scientific articles. Since this research is normative, the main focus is on the study of positive legal norms rather than empirical field data. The analysis was conducted qualitatively through categorization and deductive reasoning. The results indicate that whistleblowers play a strategic role in detecting and exposing fraudulent practices due to their direct access to internal information that is not available to the public. The fraud in question includes various forms of legal and ethical violations that occur in the banking sector and may harm customers, financial institutions, and the overall stability of the economy. From the maslahah perspective, the existence of whistleblowers represents an effort to protect the public interest, particularly in maintaining honesty, justice, and property within the muamalah (social transaction) system. The study recommends strengthening legal protection mechanisms for whistleblowers to ensure their security and prevent potential threats, intimidation, or retaliatory actions. Furthermore, the study highlights the importance of establishing a reporting system that is both technically and institutionally secure, while also oriented toward public benefit by promoting civic participation in oversight and strengthening the effectiveness of law enforcement and transparent governance.